2014
DOI: 10.1002/jmv.24073
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the prevalence of oncogenic HPV types among Lithuanian women with cervical pathology

Abstract: Human papillomavirus (HPV) is the main cause of cervical cancer. Therefore, the detection of oncogenic HPV types is important in predicting the risk of cervical cancer. The aim of the current study was to estimate the prevalence of 16 carcinogenic and potentially carcinogenic HPV types in the study group of Lithuanian women with various grades of cervical pathology in comparison to healthy women. A total of 824 cervical specimens were investigated for HPV DNA: 547 specimens of women with abnormal cytology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
(35 reference statements)
0
6
1
6
Order By: Relevance
“…Honduras'ta Tabore ve arkadaşları %88.2, Hindistan'da Baskaran ve arkadaşları %84.3, Fas'ta Assoumou ve arkadaşları %76.9, Kore'de Kim ve arkadaşları %75, Litvanya'da Simanaviciene ve arkadaşları %67.6, Venezuela'da Corenti ve arkadaşları %62, Romanya'da Corneanu ve arkadaşları %61, Çin'de Jiang ve arkadaşları %39.4 oranında bulmuşlardır. Ülkemizde Ankara'da yapılan çalışmalardan, Ergünay ve arkadaşları %80, Dursun ve arkadaşları %52, Aydoğan ve arkadaşları %50, Mersin'de yapılan çalışmada Tezcan ve arkadaşları %35.4 oranında tespit etmişlerdir [8][9][10][11][12][13][14][15][16][17][18][19] .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Honduras'ta Tabore ve arkadaşları %88.2, Hindistan'da Baskaran ve arkadaşları %84.3, Fas'ta Assoumou ve arkadaşları %76.9, Kore'de Kim ve arkadaşları %75, Litvanya'da Simanaviciene ve arkadaşları %67.6, Venezuela'da Corenti ve arkadaşları %62, Romanya'da Corneanu ve arkadaşları %61, Çin'de Jiang ve arkadaşları %39.4 oranında bulmuşlardır. Ülkemizde Ankara'da yapılan çalışmalardan, Ergünay ve arkadaşları %80, Dursun ve arkadaşları %52, Aydoğan ve arkadaşları %50, Mersin'de yapılan çalışmada Tezcan ve arkadaşları %35.4 oranında tespit etmişlerdir [8][9][10][11][12][13][14][15][16][17][18][19] .…”
Section: Discussionunclassified
“…Assoumou ve arkadaşları LSIL sitolojili kadınlarda HR HPV prevalansını %87.5, Tabora ve arkadaşları %81, Corenti ve arkadaşları %68, Simanaviciene ve arkadaşları %55.2, Jiang ve arkadaşları %43.5 olarak bulmuşlardır. Ülkemizde ise Dursun ve arkadaşları LSIL sitolojili kadınlarda HR HPV prevalansını %27, Abike ve arkadaşları %26, Aydoğan ve arkadaşları %34.5, Tezcan ve arkadaşları %42.9, Beyazıt ve arkadaşları %62, Baskaran ve arkadaşları %65.7, Ergünay ve arkadaşları %100 oranında bulmuşlardır [8][9][10]12,13,15,[16][17][18][19][20][21] . HSIL sitolojili kadınlardaki %66.7'lik HR HPV prevalansı Aydoğan ve arkadaşlarının %7'lik Dursun ve arkadaşlarının %20'lik oranından yüksek, Tezcan ve arkadaşlarının %75'lik oranına yakın, Assoumou ve arkadaşlarının %100, Ergünay ve arkadaşlarının %100, Tabora ve arkadaşlarının %97, Corenti ve arkadaşlarının %95, Kim ve arkadaşlarının %96.7, Abike ve arkadaşlarının %91, Jiang ve arkadaşlarının %90, Baskaran ve arkadaşlarının %84.6, Beyazıt ve arkadaşlarının %83 ve Simaviciene ve arkadaşlarının %80.3 oranlarından düşük tespit edilmiştir [8][9][10][11][12][14][15][16][17][18][19][20][21] .…”
Section: Discussionunclassified
“…The prevalence (including HPV negative cases in the denominator) of HPV-16 was 27.6%, 39.8%, and 58.2% and HPV-18 prevalence 9.0%, 10.0%, and 7.4% in CIN I-III cases respectively [Guan et al, 2012], again higher than the estimates reported in the present study, variation which may have arisen from methodological differences in HPV detection techniques. The majority of SCCs (92.2%) in the present study were HPV positive, this is in accordance with the proportions of invasive cervical cancers (the majority of which were SCCs) testing HPV positive in other countries of the UK [Mesher et al, 2015], Sweden, Including high-risk HPV genotypes other than HPV 16/18 that is: 33,35,39,45,51,52,56,58,59,66,and 68. Spain Italy, and Eastern Europe [Du et al, 2011;Alemany et al, 2012;Giorgi Rossi et al, 2012;Guan et al, 2012;Piana et al, 2013;Pista et al, 2013;Tjalma et al, 2013;Skamperle et al, 2013;Kjaer et al, 2014;Simanaviciene et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…Cervical samples were collected from the cervix using cervical brush during our previous study on the prevalence of oncogenic HPV types among Lithuanian women with cervical pathology (Simanaviciene et al, 2015). The study was approved by Vilnius Regional Committee of Biomedical Research (Lithuania, permission no.…”
Section: Clinical Specimens and Study Groupsmentioning
confidence: 99%
“…CRL-1550) were purified using "GeneJET ™ Genomic DNA Purification Kit" according to manufacturer's instruction. Detailed description of collected cervical specimens and the procedure of DNA extraction from cervical specimens have been presented previously (Simanaviciene et al, 2015).…”
Section: Dna Purificationmentioning
confidence: 99%